Don't destroy the environment - Braslow, Juliet; Lolig, Victor; Dittoh, Saa; Tuota, Jonathan; Akudugu, Mamudu; Abra, Edem (2016)
This participatory video titled “Don’t destroy the environment” was filmed, produced, and directed by a group of 9 farmers and community members from Kunzokalla Village in Jirapa District, Upper West Region of Ghana. With this video they want to communicate that the environment needs our active protection and management and we should all ‘rise up and fight to save the land.’ The film features farmers describing opportunities and ways to better protect the environment such as avoiding the use of herbicides, refraining from bush burning, planting trees, and protecting economically valuable tree species. Through a 6 day process facilitated by Juliet Braslow (CIAT), Victor Lolig (UDS), Saa Dittoh (UDS), Jonathan Tuota, Mamudu Akudugu (UDS), Edem Abra (UDS), the farmers learned video techniques, interviewing skills, and developed the story they wanted to share with their community, local leaders, and the world.